Investigations of low-temperature reaction pathways in solid-state reactions - Tran, Gia Thinh, author; Neilson, James R., advisor; Prieto, Amy L., committee member; Sambur, Justin B., committee member; Chen, Hua, committee member (Colorado State University. Libraries, 2024)
Advances in our technology are limited by our knowledge of functional materials, and access to new, possibly better, functional materials is limited by our synthesis methods. This dissertation discusses different synthesis methods for a variety of solid state materials. At the core of this thesis are metathesis reactions i.e. double displacement reactions. Metathesis reactions allow for control over product selectivity and reaction kinetics with choice of the spectating ions. We demonstrate these characteristics with different spectating ions in metathesis and cometathesis (e.g., combining 2 halides) reactions. LaMnO3 was chosen to probe the product selectivity of anion cometathesis towards specific off-stoichiometries of LaMnO3. The metathesis reaction for BiFeO3 illustrates that prediction of thermodynamic selectivity is important, but reaction kinetics remain important as well. Kinetic studies of metathesis reactions that form YMnO3 demonstrate the importance of crystalline intermediates to modulate the reaction rates. The complexity of solid-state kinetics their kinetic regimes within a reaction can be identified through synchrotron X-ray diffraction. We attempted to synthesize LiMoO2 as precursors for the proposed phase LaMoO3. We demonstrate our considerations on the synthesis challenges and offer gained insights into alternative Mo-based systems (nitrides). Aside from metathesis reactions, we employ learned concepts to flux reactions to influence the chemical potential of N2. Synthesis of Li-Fe-O-N and Li-Mn-O-N phases was attempted under the hypothesis that alkali halide salt mixtures solubilize nitrogen and pin nitrogen's chemical potential to prevent N2 formation. Cs2SbCl6 was chosen as a single crystal target to gain clearer insights into the electronic structure. Single crystals were synthesized via hydrothermal synthesis, but preliminary conductivity measurements suggest that Cs2SbCl6 has a photoconductance below our limit detection.
Keywords: low-temperature; metathesis; solid-state; materials; kinetics; perovskite